Narrative Discourse in Spanish: A Two Reference Points System for Verb Tense Representation - Cruz Enriquez, Maura; Lareau, François (Redis: Revista de Estudos do Discurso, 2025)
Numerous systems have been conceived to date to show the temporal meanings associated with tenses. Some of them claim to be universal but fail to represent the contrast between tenses like Spanish imperfect and pretérito. Others describe only the tenses basic meaning, excluding other narrative uses that these tenses have in discourse, and without considering the role of lexical aspect in tense selection and interpretation. This article will address this issue by proposing a new temporal system with two reference points (R and N) and two kinds of events in terms of lexical aspect (narrative and commentative). This new system makes it possible to differentiate strictly grammatical temporal relations (between the event and R) from discursive temporal relations (between the event and N), as well as to represent the multiple contextual uses of the imperfect and the pretérito of Spanish. To illustrate the narrative uses of these tenses in discourse, we provide examples from a corpus of narratives in the past produced by native Spanish speakers. The examples taken from the corpus show that the pretérito can represent both synchronous and anterior relations between events and N, but it only designates narrative processes and their perfect phase. The imperfect, for its part, represents both commentary and narrative processes, as well as the progressive phase of the latter, but seems to be limited to designating a synchronic relation between the event and the point N.